Terrorism and Global Security - Robertson, Ann E. (New Delhi Viva Books, 2010)
Provides essays, primary source documents, and research tools that explore terrorism and security around the world. Includes an annotated bibliography, a chronology, and a glossary.
Include Index
Keywords: Terrorism -- United States -- Terrorism -- Terrorism--Psychological Aspects -- United States